On the Autonomy of the Transcendental Time-Horizon: an Essay in De-Subjectivizing Heidegger's Kant-Interpretation. - Liu, Renxiang (Sophia, 2024)
In this paper, I discuss, in a Heideggerian context, the possibility of de-subjectivizing the notion of the transcendental time-horizon and reinterpreting it as a formally indicated 'whereto' of releasement. The structures of the time-horizon depict the way beings unfold in the fullness of time in their alterity, and they orient the subject's activity of 'projection.' What results is a field-oriented (as opposed to self-oriented) transcendental philosophy which would survive Heidegger's critique of his own transcendental project, and which would avoid mystification. I take three steps. First, I point out that the problematization of 'transcendental Heidegger' is based on the subjectivist interpretation of the time-horizon. I problematize a recent account in the subjectivist vein, arguing that it is neither indispensable, nor very plausible, nor the most illuminative of Heidegger's work. Second, with the help of Dahlstrom, Golob, Engelland, Sheehan, and Vasterling, I gradually dissociate the notion of the horizon from subjectivism, the visual metaphor, and the assumption of an absolute ground. I suggest instead that the horizonality of the horizon be understood temporally, i.e., as an interplay of presencing and absencing where what matter most are the structures, themselves affected by time, which the transcendental field displays when beings unfold themselves within it. Third, I identify three of those structures when performing a de-subjectivizing reading of Heidegger's interpretation of the threefold synthesis in Kant's A-Deduction. These structures capture the way every being manifests itself, without themselves being necessarily grounded in the subject's activity. This gives an example of how transcendental philosophy can clarify what the time-horizon is like while bracketing the question of its provenance.